Flouting The Conversational Maxims in A Musical Fantasy Movie - Frina Diniarta Nur (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2022)
This research aims at analyzing the occurrence of flouting the conversational maxims in the musical fantasy movie Beauty and the Beast. The study uses qualitative methods and intends to answer five research questions. The first question to answer is how often the conversational maxims are flouted in the movie. The research finds one hundred two conversations that contain flouting of the conversational maxims. The second to answer is what types of conversational maxims are flouted in the conversations in the movie. The research shows that twenty-eight conversations flout maxim of quantity, thirty-six conversations flout maxim of quality, eighteen flouts maxim of relation or relevance, and twenty conversations flout maxim of manner. The third question to answer is who flout the conversational maxims in the movie. The study reveals that sixteen characters flout the conversational maxims. Then the fourth question to answer is the characters’ reasons of flouting the conversational maxims in the movie. The research shows that the speaker flouts the maxim for various reasons according to what maxim that is flouted. Finally, this research also intends to find out the implicatures of the characters’ utterances when they flout the conversational maxims in the movie. The analysis shows that flouting of conversational maxims always generates implicature or hidden meaning. This implied meaning varies based on the speaker’s intention and the type of maxim that he/she flouts.